Three disruptive models of new spatial planning: 'attention', 'surveillance' or 'sustainable' capitalisms? - Philip Cooke (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This paper compares and contrasts three disruptive models of potential and actual new kinds of spatial planning. These include 'seasteading', 'smart neighbourhoods' and 'renewable spatial systems'. Each is labelled with distinctive discursive titles, respectively: 'Attention Capitalism'; 'Surveillance Capitalism' and 'Sustainable Capitalism' denoting the different lineaments of each, although they all have their origins in the Silicon Valley techno-entrepreneurial milieu. In each case, while the path dependences of trajectories have diverged the progenitors were often erstwhile business partners at the outset. The paper is interested in qualitative methodology and proposes 'pattern recognition' as a means to disclose the deep psychological, sociological, political and economic levels that inform the surface appearances and functions of the diverse spatial planning modes and designs that have been advanced or inferred from empirically observable initiator practice. 'Dark Triad' analysis is entailed in actualising psychological deep structures. Each of the three models is discussed and the lineaments of their initiators' ideas are disclosed. Each 'school' has a designated mentor(s), respectively: academic B. J. Fogg and venture capitalist Peter Thiel for 'Attention Capitalism', 'smart city' planner Dan Doctoroff for 'Surveillance Capitalism' and 'renewable energineer' and Elon Musk for 'Sustainable Capitalism', the eventual winner of this existential 'dark versus light triad' urban planning contest.
Keywords: 650; attention; surveillance; sustainable cities; dark triad; light triad; gigaproject